Effect of Service Quality, Price and Location on Costumers Satisfaction at Bangi Cafe Kota Wisata Cibubur - Nur Wahyuni (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to determine the effect of Service Quality, Price and Location on Customer Satisfaction at Bangi Café Kota Wisata Cibubur. The method carried out in this study is a quantitative method. The author used data collection techniques with questionnaires and given to several people who have become customers of Bangi Café itself. From data processing that has been carried out and obtained samples to 50 respondents (using convenient technique). Adjusted R-Square was obtained at 0.754. This means that the variables of service quality, price and location are able to explain 75.4% of their influence on the dependent latent variable.  The research results show that the price and service quality variables have a significant effect on customer satisfaction, but the location factor does not have an influence on customer satisfaction. Prices have a strong influence on young people whose pockets are still limited or dependent on their parents